2019
DOI: 10.1108/jabs-03-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Auditors’ professionalism and factors affecting it: insights from Indonesia

Abstract: Purpose This study aims to investigate the effects of intellectual intelligence, emotional intelligence, internal locus of control, and auditors’ experience (intrinsic characteristics) and organizational culture (an extrinsic characteristic) on auditors’ professionalism. Design/methodology/approach Data are collected from auditors working in public accounting firms in the Central Java and Yogyakarta provinces of Indonesia between March 1 and June 30, 2017, using survey questionnaires with a Likert scale (one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
15
1
1
Order By: Relevance
“…Pre-service education (Ro, 2020) and subsequent professional development (CIPC, 2020) are considered to enhance the professionalism required to meet clients’ needs. The use if class and workplace training tasks is consistent with Suyono and Farooque (2019) contention that “professionalism is behaviour that maintains work quality” (p. 545). Abou Arraj (2018) contends that “maintaining a high level of professionalism helps the employees to keep up to work standards, but it may decrease bureaucratic flexibility” (p. 387).…”
Section: Results Of Literature Review and Evident Gapssupporting
confidence: 66%
See 1 more Smart Citation
“…Pre-service education (Ro, 2020) and subsequent professional development (CIPC, 2020) are considered to enhance the professionalism required to meet clients’ needs. The use if class and workplace training tasks is consistent with Suyono and Farooque (2019) contention that “professionalism is behaviour that maintains work quality” (p. 545). Abou Arraj (2018) contends that “maintaining a high level of professionalism helps the employees to keep up to work standards, but it may decrease bureaucratic flexibility” (p. 387).…”
Section: Results Of Literature Review and Evident Gapssupporting
confidence: 66%
“…Annisette (2017) observes that professionalization is about the demarcations of boundaries as part of social closure. Suyono and Farooque (2019) consider professionalism as an ethical of occupation because practitioners are expected to comply with the ethical code of conduct. Brint (2015) and Mason (2020) distinguishes professionalism based on specialized expertise from professionalism, focusing on expert knowledge to serve goals defined by the labor marketplace.…”
Section: Results Of Literature Review and Evident Gapsmentioning
confidence: 99%
“…Beberapa penelitian terdahulu telah mengkaji secara parsial hubungan Emotional Intelligence, Intellectual Intelligence, Work Experience, Kinerja, dan Profesionalsme terhadap kinerja SDM, hasil penelitian yaitu penelitian yang menyatakan signifikan dan pengaruh positif (Ardiansyah & Sulistiyowati, 2018), (Berliana et al, 2020), (Bili et al, 2018), (Rowe, 2017), (Sitepu et al, 2020), dan studi yang menunjukkan tidak ada pengaruh yang signifikan (Akimas & Bachri, 2016), (Suyono & Farooque, 2019).…”
Section: Pendahuluanunclassified
“…Nguyen et al (2019) quantitatively conducted a survey encompassing 319 IT professionals of Vietnam and concluded that the existence of a considerable relation of organizational culture with the employee innovation and further divulged that five organizational culture’s dimensions are specifically and significantly allied with employee innovation. Suyono and Al Farooque (2019) first surveyed certain public accounting firm auditors in Indonesia in the context of their proficiencies and concluded that organizational culture does not influence auditor’s professionalism.…”
Section: Six Sigma Critical Success Factors: a Literature Reviewmentioning
confidence: 99%